The Coca-Cola Company : equity valuation - Santos, André Escoval dos (2016)
The present dissertation aims to demonstrate the process of valuing The Coca-Cola Company (KO). Valuation is not an exact science, requiring numerous assumptions and different models to be trusted. Several theories and articles from prestigious authors were followed aiming to deliver the best possible result. There is not a consensus among authors about which method yields best results, however Discounted Cash Flow is considered the finest by most of them. Therefore, KO will be valued according to the DCF model, complemented with a relative valuation, a fundamental valuation tool when used additionally. Finally a comparison is going to be made with the 21 July 2015 J.P. Morgan report, with a recommended target price of $ 46.